Unveiling the DHX15-G-patch interplay in retroviral RNA packaging - Dostálková, Alžběta; Křížová, Ivana; Junková, Petra; Racková, Jana; Kapisheva, Marina; Novotný, Radim; Danda, Matěj; Zvonařová, Karolína; Šinkovec, Larisa; Večerková, Kateřina; Bednářová, Lucie; Ruml, Tomáš; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2024)
We explored how a simple retrovirus, Mason-Pfizer monkey virus (M-PMV) to facilitate its replication process, utilizes DHX15, a cellular RNA helicase, typically engaged in RNA processing. Through advanced genetic engineering techniques, we showed that M-PMV recruits DHX15 by mimicking cellular mechanisms, relocating it from the nucleus to the cytoplasm to aid in viral assembly. This interaction is essential for the correct packaging of the viral genome and critical for its infectivity. Our findings offer unique insights into the mechanisms of viral manipulation of host cellular processes, highlighting a sophisticated strategy that viruses employ to leverage cellular machinery for their replication. This study adds valuable knowledge to the understanding of viral-host interactions but also suggests a common evolutionary history between cellular processes and viral mechanisms. This finding opens a unique perspective on the export mechanism of intron-retaining mRNAs in the packaging of viral genetic information and potentially develop ways to stop it.
Keywords: buněčné jádro; DEAD-box RNA Helicases; Mason-Pfizer monkey virus; HEK293 Cells; Virus Assembly; RNA-helikasy; DEAD-box RNA-helikasy; sestavení viru; RNA Helicases; RNA, Viral; replikace viru; Cell Nucleus; zvířata; HEK293 buňky; Humans; genom virový; Virus Replication; Masonův-Pfizerův opičí virus; RNA virová; Genome, Viral; lidé; Animals